Social Security and Pension Reform - Szczepanski, Marek; John, Turner. A. (W.E. Upjohn Institute, 2023)
Countries around the world are reforming their social security and pension systems. International studies often focus on social security reforms in Europe and North America, and may include Latin America. Reforms, however, are also occurring in Asia and Africa, and include reforms of voluntary and employer-provided pensions as well as social security programs. This book discusses both social security and employer-provided pension reforms, as well as reforms in most regions of the world.